First record of three alien Auchenorrhyncha species from Europe: Acanalonia bivittata (Say, 1825), Branchana xanthota Li, 2011, and Dryadomorpha pallida Kirkaldy 1906 (Hemiptera: Auchenorrhyncha: Acanaloniidae, Cicadellidae) - Sanna, Francesco; Poggi, Francesco (Zootaxa, 2022)
Three alien Auchenorrhyncha species are recorded for the first time from Europe (northern Italy): the Nearctic planthopper Acanalonia bivittata (Say, 1825), the Asian leafhopper Branchana xanthota Li, 2011, and the leafhopper Dryadomorpha pallida Kirkaldy 1906, present in the Afrotropical, Palearctic, Oriental and Australian regions. Observations on morphology and data on biology and host plants are provided. The 5th instar nymph of Dryadomorpha pallida is described. Considerations and data about the increase of alien Auchenorrhyncha species in Europe are discussed.